ROLE OF ANCESTORS AND WEATHER CONDITIONS IN MOISTURE SUPPLY OF DURUM WINTER WHEAT - A. S. Popov; G. V. Ovsyannikova; N. E. Samofalova; E. D. Krivosheevа (Зерновое хозяйство России)
In the southern part of the Rostov region the primary factor for favourable conditions of plants is a sufficient moisture of durum winter wheat in the vegetation period. The ancestor greatly effects on moisture of the crop during the initial vegetation period of durum winter wheat. The proper choice of the ancestor gives a stable and high yield of grain. The study of ancestors (‘winter wheat’, ‘maize for silage’, ‘peas for grain’, ‘black’ fallow’) for durum winter wheat were carried out on the trials of All-Russian Research Institute of Grain Crops after I.G. Kalinenko. The experiments determined that ‘black’ fallow’ stored the most amount of productive moisture for durum winter wheat, which supplied timely, uniform and dense germination. That’s why durum winter wheat gave the highest productivity (4,63 t/ha) sown in ‘black’ fallow’. The maximum productivity in fallow land was received when the crop was sown after ‘peas for grain’ (3,91 t/ha). The moisture consumption of durum winter wheat in ‘black’ fallow’ was 389,4 mm on average, which was on 55,3-77,9 mm more than in fallow land. Thus, the total consumption of moisture per one ton of the harvested crop in black fallow was 40% less than after ‘winter wheat’ and 8% less than after ‘maize for silage’, but it was the same after ‘peas for grain’.  The formation of durum winter wheat yield is more determined by weather conditions (76,0-95,8%), than by the choice of ancestor. In the period of vegetation the plants consume about 4,2-24,0% of productive moisture stored after ancestors.